Dinâmica populacional em diferentes escalas espaciais de duas espécies arbóreas da Floresta Atlântica - Rosa, Lucas Benedito Gonsales (Universidade Federal de São Carlos, 2018)
The population dynamics of plants can be differently influenced by environmental differences in both regional and local scales. On a regional scale, population dynamics can be influenced by climate, stochastic events and anthropogenic actions. On a local scale, dynamics can also be influenced by environmental characteristics that differ locally, such as light, topography and soil characteristics. Environmental differences in both regional and local levels are expected to have a greater effect on specialist species, which present a more restricted geographical distribution and lower local abundance than generalist species. The objective of this study was to test the spatial variation in the dynamics of different populations of two tropical tree species, with extremely different geographic distributions and local abundances, and how they responded to environmental differences on a local scale. We used data from two demographic censuses of Faramea picinguabae M.Gomes (Rubiaceae) and Mollinedia schottiana (Spreng.) Perkins (Monimiaceae), which were performed approximately 9 years apart, held in two non-contiguous, permanent 1-ha plots (B and E) located at a region of the Atlantic Rainforest, Southeast Brazil. Due to the species’ geographical distribution and local abundance, we have assumed that F. picinguabae is a specialist species and M. schottiana is a generalist species. Each plot was divided into 100 subplots, in which we measured the canopy opening, elevation, declivity, and soil coverage by rocky boulders. In order to test the existence of spatial variation in the dynamics among plots, we have compared the environmental variables among plots, where the population is defined as the group of individuals of the same species in the same plot. In turn, to test how local environmental variations influence population dynamics, we have divided each of the environmental variables into categories and defined population as the group of individuals of the same species in each of the categories. In the two previous cases, we have calculated the limited rate of annual population growth (λ). We have found differences in annual λ both among plots and among categories of environmental variables only for the specialist species. All populations presented annual λ < 1, except for F. picinguabae on plot B and in environmental categories where the canopy openings are similar and higher than the average among censuses. The population decline of most populations may be explained by the intense drought in Ubatuba in the last decade. However, on a local scale, the population growth of F. picinguabae in plot B may have occurred due to a positive response of this species to the lower soil coverage by rocky boulders, which seems to have balanced the negative consequences of the drought. The understanding of how environmental variations, acting at different scales, influence the λ of plant populations with distinct strategies is important to help predict their behavior against environmental changes. From this, further studies are needed to determine how common this variation in population dynamics is and whether it can be predicted by species strategies, aiming at management actions to stabilize or increase their population size within a forest.
Population dynamics at different spatial scales of two tree species of Atlantic Forest
Keywords: Categorias ambientais; Declínio populacional; Estrutura populacional; Floresta Ombrófila Densa de Terras Baixas; LTRE; Environmental categories; Population decline; Population structure; Lowland Ombrophilous Dense Forest; CIENCIAS AGRARIAS